Spontaneous Pneumomediastinum – a Rare Asthma Complication - Serghei Covantev; Natalia Mazuruc; Rasul Uzdenov; Alexandru Corlateanu (Folia Medica, 2019)
Asthma is the most common chronic respiratory disease worldwide and its prevalence is increasing. Acute asthma complications are often the reason for admission to emergency healthcare service. In our article we present a case of a rare asthma complication – spontaneous pneumomediastinum with a short review of its incidence, etiology, diagnosis and management. Spontaneus pneumothorax is important to differentiate with secondary pneumomediastinum as well as other conditions as cardiac diseases (acute coronary syndrome, pericarditis, cardiac tamponade, pneumopericardium), lung diseases (pneumothorax, pulmonary embolism, tracheobronchial tree rupture), musculoskeletal disorders, and diseases of the esophagus (rupture and perforation o the esophagus). A chest X-ray is often reliable for diagnosis of spontaneous pneumomediastinum and when inconclusive, can be followed by CT. The management is usually conservative with oxygen and analgesia. Surgery is required only in cases of tracheobronchial compression.